A review on the advancement of human powered flywheel motor (HPFM) in India and its application for rural empowerment. (2020) - Kumar Dubey, Harrsh; Singh, M.P.; Modak, J.P.; Makade, Rahul
Abstract: The modern world is continuously focusing on a carbon-free atmosphere to improve environmental sustainability. In the last two decades, Human Powered Flywheel Motor has been applied to design numerous rural-based applications. The functional feasibility and economic viability of Pedal-powered process machines of 3 to 5 Horse Power capacity over motorized machines have increased the utility for rural-based applications. The present work deals with the review of various research investigations done on the Human Powered Flywheel Motor system. Further, the conversion of the Human Powered Flywheel Motor into the electromechanical analog circuit and the generation of design data for Human Powered Flywheel Motor through the establishment of generalized experimental data-based models have also been discussed. It is concluded that the Human Powered Flywheel Motor can generate a maximum of 3 to 5 Horse Power, which can be utilized against the various motorized machines in rural applications where intermittent power supply does not affect the end quality of the product.